PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH DENGAN MEMANFAATKAN AUTOPLAY UNTUK MENINGKATKAN HASIL BELAJAR TEMA VIII PERISTIWA ALAM SD/MI - Trisnaning Legiowati; Asri Widiatsih; Fajarisman Fajarisman (STKIP PGRI Situbondo, 2023)
Abstract: Based on the results of initial observations in class I SDN 2 Wonokoyo, learning outcomes on natural events are still low. This is caused by factors, one of which is the lack of using a learning model. To find a solution to solve the problem is to use the Make A Match by utilizing Autoplay. The research objectives are 1) To know the activities of teachers and students in using the Make A Match students responses to the application of the Make A Match for Natural Events 3) To find out how the learning outcomes are after using the Make a Match. Research is a classroom action that includes 4 stages of planning, implementation, observation and reflection. Research Subjects at SDN 2 Wonokoyo Class I, totaling 20 students. The results of the study obtained the value of student activities to operate the learning media Autoplay Cycle I 63, 33% Cycle II 78, 82. Cooperation 68. 79% Cycle I and Cycle II 86. 78%, Asking 65. 55% Cycle I while Cycle II 81. 17%. By using the Make A Match model with Autoplay, many people were interested and the learning outcomes in the first cycle were 12 with 60%, while the second cycle increased by 95% with 19 students completing. learning model Make A Match it can improve teacher abilities, improve learning abilities and outcomes